Adsorpcija Cd(II), Pb(II), Cu(II) i Zn(II) na okside, gline i kalcit : doktorska disertacija - Kozar, Sonja; Bilinski, Halka; Kallay, Nikola; Lovrić, Milivoj; Filipović-Vinceković, Nada (Zagreb : S. Kozar, 1995)
Sažetak: U svrhu boljeg razumijevanja ciklusa nekih tragova kovina u morskom okolišu ispitivana je adsorpcija iona kovina Cd(II), Pb(II), Cu(II) i Zn(II) na različite adsorbense. Eksperimenti na modelnim oksidima SiO2, [gama]-Al2O3 i MnO2 u morskoj vodi pokazali su da adsorpcija ispitivanih kovina opada u nizu: SiO2 (Zn(II)]]Pb(II)]Cu(II)]]Cd(II)); [gama]-Al2O3 (Zn(II)]Cu(II)]Pb(II)]]Cd(II)); MnO2 (Pb(II)]Cu(II)]]Zn(II)]Cd(II)).Podaci su prikazani u obliku Langmuirove adsorpcione izoterme. Ispitivanje adsorpcije Cu(II) u morskoj vodi na [gama]-Al2O3 u prisustvu EDTA pokazalo je da se Cu-EDTA kompleks ne adsorbira, za razliku od labilnih ionskih Cu-kompleksa. Adsorpcija tragova kovina Pb(II), Cu(II) i Zn(II) na kaolin i bentonit ispitivana je u različitim razrjeđenjima morske vode.
U vodi niskog saliniteta primijećena je jaka adsorpcija svih kovina dok je u morskoj vodi, za razliku od ostalih kovina, adsorpcija kadmija zanemarljiva. Inhibicija adsorpcije Cd(II) na bentonit u morskoj vodi se smanjuje u redu Mg2+]Ca2+]Sr2+ i Cl-]Br- I- SO42- SiO42-. Organska tvar prisutna u morskoj vodi, kao i neke modelne organske tvari, inhibiraju adsorpciju kadmija na bentonit, dok površinsko aktivne tvari na nju ne utječu. Ispitivana je adsorpcija Pb(II) i Cd(II) na kalcit u prirodnoj vodi uzorkovanoj u estuariju rijeke Krke (saliniteta 3, 14, 20 i 38[promila]. Dobiveni rezultati pokazuju da se olovo i kadmij vežu na različita mjesta na kalcitu, tako da je adsorpcija olova jaka kod svih saliniteta, a za kadmij naglo opada s porastom saliniteta.
Za prikaz adsorpcije na kalcit testirano je nekoliko adsorpcijskih modela, kao što su Freundlich-ov, Langmiur-ov i Schindler-Stumm-ov površinsko koordinacijski model. Nađeno je da adsorpcijske izoterme pripadaju klasi S-1 empirijskih adsorpcijskih izotermi, što je objašnjeno efektom veličine čestica adsorbensa.
Summary: For a better understanding of geochemical cycles of some trace metal ions in the marine environment, the adsorption of Cd(II), Pb(II), Cu(II) and Zn(II) has been studied on various adsorbents. Experiments on model oxides surfaces, SiO2, [gama]-Al2O3 and MnO2 in seawater showed a following order of the adsorption: SiO2 (Zn(II)]]Pb(II)]Cu(II)]]Cd(II)); [gama]-Al2O3 (Zn(II)]Cu(II)]Pb(II)]]Cd(II)); MnO2 (Pb(II)]Cu(II)]]Zn(II)]Cd(II)). Data are presented in the form of Langmuir adsorption isoterms. Study of the adsorption of Cu(II) in seawater on [gama]-Al2O3 in the presence of EDTA showed that Cu-EDTA complex is not adsorbed, in contrast to the labile ionic Cu-complexes. The adsorption of trace metals Pb(II), Cu(II) and Zn(II) on clays kaolinite and bentonite has been studied in seawater of various dilutions.
Under freshwater conditions both Cd(II) and Pb(II) are well adsorbed, whereas under seawater conditions, in contrast to other metals, adsorption of cadmium is negligible. The inhibition of Cd(II) adsorption on bentonite by seawater macroconstituents decreases in the order Mg2+]Ca2+]Sr2+ and Cl-]Br- I- SO42- SiO42-. Organic ligands of marine origin, as well as some model organic supstances,reduce cadmium adsorption, while artificial surface active substances show no effect. The adsorption of Pb(II) and Cd(II) ions on calcite in natural water from the calcareous Krka river (salinities 3, 14, 20 and 38 ) was investigated.
The results suggest that the two ions are adsorbed at different calcite surface sites; Pb(II) remained firmly bound to calcite at all salinities, whereas Cd(II) was firmly bound at low salinities and released at high salinities. Several adsorption models were tested, such as Freundlich's, Langmuir's and Schindler-Stumm's surface coordination model. Adsorption isotherms belong to S-1 class of empirical adsorption isotherms, which was explained as a particle size effect.
Doktor prirodnih znanosti - kemija
mentor: Halka Bilinski; Komisija za ocjenu: Halka Bilinski, Nikola Kallay, Milivoj Lovrić, Nada Filipović-Vinceković; Komisija za obranu: Nikola Kallay, Halka Bilinski, Nada Filipović-Vinceković; datum obrane: 21.03.1995; datum promocije: 30.06.1995.
Sveučilište u Zagrebu, Institut "Ruđer Bošković", Zagreb, 1995
Bibliografija: str. 80-87
Summary
Keywords: Metali -- Apsorpcija i adsorpcija